Avaliação do ruído urbano : o caso da área central de Passo Fundo-RS - Fritsch, Rodrigo Carlos (2006)
The present study describes the result of a research in exploratory level that was carried out in a central area in Passo Fundo, Rio Grande do Sul, and tries to evaluate the actual noise pollution state at rush diurnal schedules in four spots in this city. The study compares the data that were obtained with the town legislation and the brazilian standards in force and with the recommendations of the World Health Organization (WHO). The results are compiled and sistematized through statistical analysis, contributing with subsidies for the conscious planning of urban development in Passo Fundo, as well as it can stablish urban and constructive recommendations for this city and other ones of medium scale